Assessment of dose contribution to pelvic lymph nodes in patients undergoing brachytherapy for carcinoma cervix - Deepak Sharma; Amrut S Kadam; Ramashish Kumar; Raghavendra BK; Srihari G; Perpetua Shruthi A; Varun Chandra (Asian Journal of Medical Sciences, 2024)
Background: The inclusion of pelvic lymph node (PLN) metastasis in the FIGO staging system has impacted disease classification and patient survival. Brachytherapy is a key component in managing carcinoma cervix; however, the dose contribution of brachytherapy to PLNs remains unclear. Aims and Objectives: This study aims to quantify the dose contribution of high-dose rate (HDR) brachytherapy to individual pelvic nodal groups. Materials and Methods: We included 40 biopsy-proven carcinoma cervix patients, stages IIA to IVA. All patients underwent external beam radiotherapy (EBRT) with concurrent cisplatin chemotherapy, followed by HDR brachytherapy, either intracavitary brachytherapy (ICBT) or interstitial brachytherapy (ISBT). A total dose of 21 Gy in 3 fractions (7 Gy per fraction) was prescribed to the high-risk clinical target volume. Results: For ICBT, the mean absolute doses received by the external iliac, internal iliac, and obturator groups were 0.56 Gy, 1.02 Gy, and 1.22 Gy, corresponding to EQD2 (α/β=10) values of 0.49 Gy, 0.93 Gy, and 1.14 Gy, respectively. In the ISBT group, the mean absolute doses were 0.49 Gy, 0.86 Gy, and 1.11 Gy, with corresponding EQD2s of 0.43 Gy, 0.85 Gy, and 1.02 Gy. Conclusion: PLNs received significant dose contributions from HDR brachytherapy in cervical cancer patients, providing valuable reference data for determining the EBRT boost dose in cases of enlarged PLNs.